Angeli e a República dos Bananas: representações cômicas da política brasileira na revista Chiclete com Banana (1985-1990) - Silva, Keliene Christina da (2011)
The present study has the goal to analyze the comic representations produced by the cartoonist Angeli about Brazilian politics, within a period which starts in 1985, with Brazil's re-democratization, until 1990. We used the twenty four issues of bi-monthly magazine series Chiclete com Banana as source for our research, through the analysis of the examples we selected images which proportioned us to build a small panorama of the chosen period, whose refers throughout the years the publication lasted. This research established itself on the usage of charges, comic stripes and cartoons produced by the artist as testimonials of his era, identifying these as a neutral approach impregnated with meaning, corresponding to the artist's point of view but also considering his insertion in a social and professional group within the scope of his production, This study is bound to the line of research Teaching of History and Historical Knowledge from the Postgraduate Program of the Federal University of Paraíba, concentrated on History and Historical Culture , through this study we strive for outlining the main characteristics of the new political situation configured after the ending of the military regime in Brazil, from the point of view of the referred artist, his perception and his critical perspective about the politics and the politicians of the New Republic.